2020
DOI: 10.1007/s10661-020-8158-9
|View full text |Cite
|
Sign up to set email alerts
|

Ambient bioaerosol distribution and associated health risks at a high traffic density junction at Dehradun city, India

Abstract: Traffic junctions are one of the crowded places where commuters are at high risk of developing respiratory infections, due to their greater exposure to airborne and human transmitted microbial pathogens. An airborne bioaerosol assessment study was carried out at a high traffic density junction focusing on their concentration, contribution in respirable particulate matter (PM), and factors influencing the distribution and microbial diversity. Andersen six-stage viable cascade impactor and a wide-range aerosol s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Unlike this study, current data shows the highest bacterial concentration at the start of the fall season (August) and the lowest in the winter however fungal abundance the follow the same pattern (Frankel et al, 2012 ). (Madhwal et al, 2020 ) monitored the bioaerosols near Bus station and an almost similar trend was recorded in all the seasons. Aspergillus, Penicillium , and Cladosporium were the most dominant fungi; however, Micrococcus, Staphylococcus, , and Bacillus were the most dominant bacterial genera (Madhwal et al, 2020 ), and the same results were shown in the monitoring of indoor air of pharmacy (Jankowiak et al, 2020 ).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Unlike this study, current data shows the highest bacterial concentration at the start of the fall season (August) and the lowest in the winter however fungal abundance the follow the same pattern (Frankel et al, 2012 ). (Madhwal et al, 2020 ) monitored the bioaerosols near Bus station and an almost similar trend was recorded in all the seasons. Aspergillus, Penicillium , and Cladosporium were the most dominant fungi; however, Micrococcus, Staphylococcus, , and Bacillus were the most dominant bacterial genera (Madhwal et al, 2020 ), and the same results were shown in the monitoring of indoor air of pharmacy (Jankowiak et al, 2020 ).…”
Section: Resultsmentioning
confidence: 58%
“…(Madhwal et al, 2020 ) monitored the bioaerosols near Bus station and an almost similar trend was recorded in all the seasons. Aspergillus, Penicillium , and Cladosporium were the most dominant fungi; however, Micrococcus, Staphylococcus, , and Bacillus were the most dominant bacterial genera (Madhwal et al, 2020 ), and the same results were shown in the monitoring of indoor air of pharmacy (Jankowiak et al, 2020 ). Fungal aerosols started declining from July–August, which may be due to increased soil moisture and hence, decreased resuspension of fungi in these months (Fan et al, 2017 ; Rathnayake et al, 2017 ).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Samples are normally collected on petri plates with growth medium, filter or liquid. Many aerobiologists have reported using six-stage cascade impactor for bioaerosol sampling in landfill sites (Akpeimeh et al 2019 ; Fraczek et al 2017 ; Fraczek and Kozdroj 2016 ; Kaarakainen et al 2008 ; Lenart-Boron 2020 ; Madhwal and Prabhu 2020 ). The duration of sampling selected should be sufficient to produce 30–100 colonies per plate (Madhwal et al 2020 ).…”
Section: Bioaerosol Sampling Techniquesmentioning
confidence: 99%
“…By long-distance transport, the northeast monsoon originating from the Asian continent could transport PM 10 and PM 2.5 , passing through Taiwan (from north to south) to downstream southern areas from autumn to the following spring annually [ 14 , 15 ]. Sandstorm dust is a prolific source of PM 10 , PM 2.5 , and bioaerosols including Aspergillus , other fungi, and bacterial isolates [ 14 , 15 , 16 ]. Therefore, urban air pollution depends greatly on seasonality and monsoons [ 17 ].…”
Section: Discussionmentioning
confidence: 99%